Local strategical tasks in the Hungarian fruit production with respect to the global economic and climatic changes - Soltész, Miklós; Nyéki, József; Szabó, Zoltán (Acta Agraria Debreceniensis, 2005)
After identifying the problems, we have determined the local tasks which Hungarian fruit growing has to accomplish to remain competitive despite global market pressures and global climate change.Fruit growing in the Great Plain is of determining importance in Hungary as 75% of fruit originates from the Great Plain. Therefore, the maintenance of the competitiveness of fruit growing on the Great Plain is an important economic interest which is a difficult task to resolve, because the global economic pressure against local resources and climate change affect the fruit growers sensitively. In Hungarian fruit production, it is necessary to select/develop with great care the appropriate location, training system and methods of emergency technology which have to be harmonised.